2017
DOI: 10.5863/1551-6776-22.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Amikacin Pharmacokinetics in Neonates Following Implementation of a New Dosage Protocol

Abstract: OBJECTIVESThe primary aim was to compare attainment of goal serum amikacin concentrations using two dosage regimens in patients admitted to a neonatal intensive care unit. Secondary objectives included comparison of percentages of supratherapeutic trough concentrations, and subtherapeutic and supratherapeutic peak concentrations. METHODSThis was an Institutional Review Board-approved, retrospective study of neonates receiving amikacin during January-December 2013 (group 1) and January-December 2014 (group 2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Amikacin is used to treat infections in neonates, including preterm neonates [ 42 , 125 , 145 , 146 , 147 ]. Although it has been successful in treating infections caused by multidrug resistant strains [ 126 , 148 , 149 ] there are still controversies about dosage and pharmacokinetics [ 126 , 146 ]. Unfortunately, the recent rise in resistance to amikacin limits the effectivity of many interventions during outbreaks of infection in neonates [ 41 , 42 , 150 ].…”
Section: Amikacinmentioning
confidence: 99%
“…Amikacin is used to treat infections in neonates, including preterm neonates [ 42 , 125 , 145 , 146 , 147 ]. Although it has been successful in treating infections caused by multidrug resistant strains [ 126 , 148 , 149 ] there are still controversies about dosage and pharmacokinetics [ 126 , 146 ]. Unfortunately, the recent rise in resistance to amikacin limits the effectivity of many interventions during outbreaks of infection in neonates [ 41 , 42 , 150 ].…”
Section: Amikacinmentioning
confidence: 99%
“…Many previous reports have shown that potential adverse effects, including nephrotoxicity in amikacin, were no more than gentamicin in neonates. 38–40 We suggest that modification of current empiric antibiotics for amikacin-based regimens should be considered, mainly in newborn infants with Gram-negative bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…PK profiles of flomoxef and amikacin were designed to have half-lives of 2.3 and 7 h, with C max values of 50 and 40 mg/L, respectively, to reflect the median neonatal time–concentration profile following an administration of 20 mg/kg IV dose of flomoxef 31 and 15 mg/kg amikacin. 40 These were determined from the sources used to determine the half-life, as described earlier. Each individual experiment consisted of four arms; monotherapy arms for both flomoxef and amikacin, a combination therapy arm and an untreated control.…”
Section: Methodsmentioning
confidence: 99%